EFFECT OF INTELLECTUAL CAPITAL, CAPITAL STRUCTURE AND MANAGERIAL OWNERSHIP TOWARD FIRM VALUE OF MANUFACTURING SECTOR COMPANIES LISTED IN INDONESIA STOCK EXCHANGE (IDX) PERIOD 2010-2014 - Hamidah, Hamidah; Ahmad, Gatot Nazir; Aulia, Rahma (Fakultas Ekonomi, Universitas Negeri Jakarta, 2015)
The purpose of this study is to know the effect of Intellectual Capital, Capital Structure and Managerial Ownership on Firm Value in Manufacturing Company Listed on Indonesia Stock Exchange in 2010-2014. In this research, intellectual capital can be seen from VACA (Value Added Capital Employed), VAHU (Value Added Human Capital), and STVA (Structural Capital Value Added). The research model in this study employs panel data analysis. The samples are manufacturing companies listed in Indonesian Stock Exchange in 2010-2014 selected by purposive sampling. The result show that VACA and STVA has negative and not significant effect on firm value (Tobins’Q). Whereas, VAHU have positive and not significant effect on firm value. Capital structure (DAR) have positive and significant effect on firm value. Managerial ownership (MGRL) have negative and significant effect on firm value. Keywords: Firm Value, Intellectual Capital, VACA, VAHU, STVA, Capital Structure, Managerial Ownership.